HTML5 game development from the ground up with Construct 2 - Dillon, Roberto (CRC Press, 2014)
Written for the new generation of hobbyists and aspiring game developers, HTML5 Game Development from the Ground Up with Construct 2 shows you how to use the sophisticated yet user-friendly HTML5-based game engine Construct 2 to develop and release polished, two-dimensional games on a multitude of different platforms. The book also covers the foundational knowledge of game analysis and design based on the author's research and teaching experiences at DigiPen Institute of Technology, James Cook University, and other institutions. The author first helps you understand what really matters in games. He guides you in becoming a better game designer from the ground up, being able to play any game critically, and expressing your ideas in a clear and concise format. The book then presents step-by-step tutorials on designing games. It explains how to build an arcade-style game as well as a platformer integrating some physics elements. It also shows you how to create a more complex puzzle game--the author's own published game, Turky on the Run . Lastly, the book discusses different ways to deploy and monetize games across several platforms, including Facebook, iOS, Android, and web-based marketplaces. Sample Construct 2 project files for the games designed in the book are available on the author's website. Integrating hands-on guidance with theoretical game design concepts, this book gives you a solid foundation in game development. It will help you advance in your journey as an indie game developer.